The Deficit of Legal Effectiveness: A Juridical Review of Illegal Dental Practice by Non-Dentist Practitioners in Indonesia - Juliantary, Sella Romika; Jamaludin, Ahmad (LifeSciFi, 2025)
The rise of dental procedures performed by non-dentists, especially high-risk aesthetic services such as illegal braces and veneer installations, has created significant legal and public health concerns in Indonesia. This study provides a juridical assessment of unauthorized dental practice and evaluates the effectiveness of law enforcement through the illegal veneer case in Karanganyar based on Decision Number 51/Pid.Sus/2019/PN.Krg). Using a normative juridical method with statutory and case approaches, it analyzes the hierarchy and consistency of relevant regulations, including the health law, medical practice law, and the Ministry of Health regulation on dental technicians. Guided by Soerjono Soekanto’s theory of law enforcement effectiveness, the findings show that such practices remain widespread due to inconsistent application of administrative and criminal sanctions, weak coordination among law-enforcement and health authorities, and low public legal awareness. The Karanganyar decision illustrates how lenient penalties and the absence of automatic administrative measures, such as closing the illegal practice undermine deterrence. The study concludes that effective enforcement of health law requires stronger institutional integration and improved legal culture. It proposes developing an integrated sanction system that links criminal rulings with mandatory administrative penalties to enhance deterrence and curb illegal dental practice nationwide.